Serum Oxytocin in Cows Is Positively Correlated with Caregiver Interactions in the Impossible Task Paradigm - Biagio D’Aniello; Vincenzo Mastellone; Claudia Pinelli; Anna Scandurra; Nadia Musco; Raffaella Tudisco; Maria Elena Pero; Federico Infascelli; Alfredo Di Lucrezia; Pietro Lombardi (Animals, 2022)
This study explored a possible relationship between the circulating oxytocin, cortisol, and the willingness of dairy cows to engage in social behaviors with humans in an experimental context. The behaviors of twenty-nine cows were recorded during the impossible task paradigm, a procedure aimed at creating a violation of expectancy, in the presence of the caregiver and a stranger. The results showed that serum oxytocin levels were positively correlated with duration and negatively correlated with the latency of the cows’ social interactions with the caregiver. This research provides a clear correlation between circulating oxytocin and a willingness to engage in social contact with the caregiver, excluding the possible effect of different cortisol levels on such behavior.